Effects of cardamonin on the growth performance, intestinal barrier function and intestinal microbiota of Danzhou chickens under heat stress - Haoran Jiang; Liguang Shi; Tanjie Deng; Guanyu Hou; Wenjuan Xun (Poultry Science)
ABSTRACT: The aim of this study was to investigate the effects of cardamonin (CDN) on the growth performance, intestinal mucosal barrier function and intestinal microbiota of Danzhou chickens under heat stress. A total of 200 one-day-old female Danzhou chickens were randomly divided into 5 groups. The daytime temperature of heat stress (HS) was set at 36 ± 2°C, and the nighttime temperature was kept the same as in the control (CON) group at 25 ± 2°C. The formal experiment lasted for 21 d. The CON and HS groups were fed a basal diet, whereas the L-CDN, M-CDN, and H-CDN groups received a basal diet supplemented with 50, 100, and 200 mg/kg CDN, respectively. Compared with the HS group, the CDN group presented a significantly greater average daily gain (ADG) (P < 0.001) but a significantly lower feed-to-gain ratio (F/G) (P = 0.007). CDN supplementation also increased the villus height (VH) and the ratio of the villus height to crypt depth (V/C) (P < 0.001) and reduced intestinal permeability by increasing expression of the ZO-1 (P < 0.001), Occludin (P < 0.001), and Claudin-1 (P = 0.034) proteins and decreasing the content of D-lactic acid (D-LA) and the activity of diamine oxidase (DAO) in serum (P < 0.001). Additionally, CDN reduced the levels of the intestinal mucosal inflammatory factors (IL-1β (P = 0.031), IL-6 (P = 0.003), and TNF-α (P = 0.014)) while upregulating IL-10 (P < 0.001). Furthermore, it increased the total antioxidant capacity (T-AOC) (P = 0.004) and catalase (CAT) activity (P < 0.001) and reduced the malondialdehyde (MDA) content (P = 0.017), effectively reducing intestinal oxidative stress and inflammatory reactions. Expression of the Nrf2 pathway-related proteins Nrf2 (P = 0.012), HO-1 (P = 0.008), and NQO1 (P = 0.003) was also increased by CDN. Moreover, feeding CDN increased the proportion of beneficial bacteria such as Firmicutes and Bacteroidetes but decreased the proportion of harmful bacteria such as Proteobacteria, thus protecting the intestinal barrier. In summary, 200 mg/kg CDN in the diet improved growth performance, enhanced intestinal barrier function and improved intestinal flora disorders in heat stress-induced Danzhou chickens, which may be related to the Nrf2/NQO1 signaling pathway.